2017
DOI: 10.1371/journal.pone.0189112
|View full text |Cite
|
Sign up to set email alerts
|

Changes in social capital and depressive states of middle-aged adults in Japan

Abstract: The present study examines the relationships between changes in bonding and bridging types of social capital and depressive states among middle-aged adults in Japan using a nationally representative sample. Data was collected from a nationwide, population-based survey conducted from 2005 to 2013 in nine annual waves. A total of 16,737 middle-aged men and 17,768 middle-aged women provided data. They reported about depressive states, measured by Kessler 6 scores, and bonding and bridging types of social capital,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Elderly individuals with a good sense of social trust have the lower likelihood of reporting anxiety, because they can obtain more information and emotional support from the person around them to handle problems, which, in turn, reduces anxiety ( 60 ). Moreover, there is evidence that people with higher levels of social trust are more likely to report good health, which plays a protective role in reducing anxiety ( 61 ). To a certain extent, a higher level of social trust could protect the elderly from the adverse impact of negative emotion by acting as a “buffer” and preventing development of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly individuals with a good sense of social trust have the lower likelihood of reporting anxiety, because they can obtain more information and emotional support from the person around them to handle problems, which, in turn, reduces anxiety ( 60 ). Moreover, there is evidence that people with higher levels of social trust are more likely to report good health, which plays a protective role in reducing anxiety ( 61 ). To a certain extent, a higher level of social trust could protect the elderly from the adverse impact of negative emotion by acting as a “buffer” and preventing development of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the negative effects of a loss of social participation were observed in both sexes [ 23 ]. A report which examined the relationship between the changes in social capital and depression observed that changes in social capital were important in the prevention of depression [ 24 ]. Based on these reports and findings that self-related health and depressive symptoms increased the risk of mortality [ 25 , 26 , 27 ], continued social participation may prevent depressive symptoms and other health problems, maintain health, and provide a protective effect against mortality.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kawachi et al [10] found the association between social trust and total mortality in the United States. Hamano et al [11] and Nakamine et al [12] found a relationship between SC and mental health in Japan, and Ferlander et al [13] reported the relationship between SC and self-perceived health in Russia. In Asia, Chuang et al [14] observed a relationship between SC and drinking and smoking as lifestyle habits in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, Chuang et al [14] observed a relationship between SC and drinking and smoking as lifestyle habits in Taiwan. Hamano et al [11] and Nakamine et al [12] found a relationship between SC and mental health in Japan. For the studies of cognitive function in Asia, Wang et al [7] found a relationship between SC and mild cognitive impairment in China.…”
Section: Introductionmentioning
confidence: 99%